Perbandingan Kinerja Keuangan PT. Unilever dan Mandom Tahun 2021-2022 Berdasarkan Rasio Likuiditas, Solvabilitas dan Profitabilitas - Cahyono, Harry; Kurniasari, Riza; Dus Reis Doa, Ajita Da Silva; Kon, Iknasius; Hermuningsih, Sri (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to compare the performance of PT Unilever Indonesia Tbk with PT Mandom Indonesia Tbk in terms of liquidity, solvency and profitability ratios. This type of research data is secondary data obtained from the idx.co.id page. The data analysis used is liquidity ratio analysis which consists of the current ratio and quick ratio; solvency ratio consisting of debt to asset and debt to equity ratios; as well as profitability ratios consisting of profit margin, return on assets, and return on equity. The research results show that PT Unilever Indonesia Tbk is superior in terms of profitability, while PT Mandom Indonesia is superior in terms of liquidity and solvency.